World-class university: students perception on service quality and satisfaction level / Noorimah Misnan, Zainuddin Zakaria & Wan Anisabanum Salleh - Misnan, Noorimah; Zakaria, Zainuddin; Salleh, Wan Anisabanum (2018)
In this paper, the authors aim to investigate the elements of service quality process and the learning outcome and its relationship to student’s satisfaction level at a public university in Malaysia. A total of 280 questionnaires were completed and returned by final year students of various courses. Items in the questionnaire were design to measure the student’s perceptions on the quality of physical facilities and the service quality of the academic and non-academic staff of UiTM Dungun campus, Terengganu. The service quality dimensions include reliability, responsiveness, assurance and empathy delivered by the staff of UiTM Dungun Campus. Furthermore, the student’s satisfaction levels were also evaluated based on the service delivery and the quality of the physical facilities. Result indicated that there is significant and positive correlation between the quality of physical facilities and all service quality elements with the satisfaction level of the students. Further analysis using the Multiple Regression analysis revealed that the assurance, empathy and reliability were positively significant in influencing the student’s perception on their satisfaction level. These results also revealed the three most important service quality dimensions that the management and staff of UiTM Dungun campus take serious consideration in increasing student’s satisfaction level The research findings may benefit both the university and students. It will help the university to determine the level of student satisfaction and to serve students more effectively in order to ensure that the university remains competitive. Such findings should help higher learning institutions to improve their service quality delivery and plan for better strategic plan to achieve a world class status.